The Effect of CSR on Stock Performance: New Evidence for the USA and Europe - Urs von Arx; Andreas Ziegler (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
This paper provides new empirical evidence for the effect of corporate social responsibility (CSR) on corporate financial performance. In contrast to former studies, we examine two different regions, namely the USA and Europe. Our econometric analysis shows that environmental and social activities of a firm compared with other firms within the industry are valued by financial markets in both regions. However, the respective positive effects on average monthly stock returns between 2003 and 2006 appear to be more robust in the USA and, in addition, to be nonlinear. Our analysis furthermore points to biased parameter estimations if incorrectly specified econometric models are applied: The seemingly significantly negative effect of environmental and social performance of the industry to which a firm belongs vanishes if the explanation of stock performance is based on the Fama-French threefactor or the Carhart four-factor models instead of the simple Capital Asset Pricing Model.
Keywords: Q56; M14; G12; Q01; 330; Corporate social responsibility; Environmental performance; Financial performance; Asset pricing models; Corporate Social Responsibility; Unternehmenserfolg; CAPM; Theorie; Schätzung; USA; Europa